2011
DOI: 10.1111/j.1747-0285.2010.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Evaluation of New N-acylhydrazones Containing Glycine Residue

Abstract: N-acylhydrazones containing glycine residue 3a-j and 8a-h were synthesized as HIV-1 capsid protein assembly inhibitors. The structures of the novel N-acylhydrazone derivatives were characterized using different spectroscopic methods. Antiviral activity demonstrated that compound 8c bearing 4-methylphenyl moiety was the most active with low cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…IR spectral data of compounds 4 – 24 were also confirmed on the basis of IR spectral data in the literature 30, 36. The bands between 1676 and 1666 cm −1 were attributed to the CO stretching bands and the bands between 1612 and 1577 were assigned to CN stretching bands of acylhydrazones 4 – 24 .…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…IR spectral data of compounds 4 – 24 were also confirmed on the basis of IR spectral data in the literature 30, 36. The bands between 1676 and 1666 cm −1 were attributed to the CO stretching bands and the bands between 1612 and 1577 were assigned to CN stretching bands of acylhydrazones 4 – 24 .…”
Section: Resultsmentioning
confidence: 57%
“…Acylhydrazones have served as starting compounds for diverse heterocyclic ring structures and have been attributed with various biological activities 10 such as antituberculosis 11–18, antibacterial 19, 20, antiparasitic 21, 22, anticancer 23–26, analgesic, and anti‐inflammatory 27–29. Further, the anti‐HIV activity of acylhydrazone scaffold compounds has been appraised in a limited number of studies 30–35 and analysis of their structures has revealed the presence of amino acid side chains (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The precursors arylsulfonylaminoacetic acid hydrazide (1), phenylsulfonylacetic acid (3), benzoylaminoacetic acid (4) and phenylsulfonylaminoacetic acid (5) were prepared according to the literature methods [20][21][22] and commercially available phenylacetic acid (2) was used as such. The cyclocondensation of 1 with 2 in the presence of POCl 3 led to 2-arylsulfonylaminomethyl-5-benzyl-1,3,4-oxadiazole (6).…”
Section: Resultsmentioning
confidence: 99%
“…N ‐Acylhydrazones, which are readily obtained by the condensation of aldehydes or ketones and acylhydrazines in the presence of an acid catalyst, represent a class of azomethine compounds . N ‐Acylhydrazones, which include the fragment (–CO–NH–N=CH–), have been the subject of much interest in recent years because of their biological properties as well as their chelating properties toward metal ions . In addition, acylhydrazones have a number of metal‐binding sites and can act as neutral or monoanionic bidentate or tridentate ligands, depending on the substituents and the reaction conditions, making them attractive as ligands .…”
Section: Introductionmentioning
confidence: 99%